Continuous therapy versus fixed duration of therapy in patients with newly diagnosed multiple myeloma - Palumbo, A.; Gay, F.; Cavallo, F.; Raimondo, F.D.; Larocca, A.; Hardan, I.; Nagler, A.; Petrucci, M.T.; Hajek, R.; Pezzatti, S.; Delforge, M.; Patriarca, F.; et al. (Journal of Clinical Oncology, 2015)
Purpose: Continuous therapy (CT) prolongs progression-free survival 1 (PFS1; time from random assignment until the first progression or death), but chemotherapy-resistant relapse may negatively impact overall survival (OS). Progression-free survival 2 (PFS2; time from random assignment until the second progression or death) may represent an additional tool to estimate outcome. This study evaluates the benefit of novel agent-based CT versus fixed duration of therapy (FDT) in patients with newly diagnosed myeloma. Methods: We included patients enrolled onto three phase III trials that randomly assigned patients to novel agent-based CT versus FDT. Primary analyses were restricted to the intent-to-treat population eligible for CT (patients progression free and alive at 1 year after random assignment). Primary end points were PFS1, PFS2, and OS. All hazard ratios (HRs) and 95% CIs were adjusted for several potential confounders using Cox models. Results: In the pooled analysis of the three trials, 604 patients were randomly assigned to CT and 614 were assigned to FDT. Median follow-up was 52 months. In the intent-to-treat CT population, CT (n = 417), compared with FDT (n = 410), significantly improved PFS1 (median, 32 v 16 months, respectively; HR, 0.47; 95% CI, 0.40 to 0.56; P < .001), PFS2 (median, 55 v 40 months, respectively; HR, 0.61; 95% CI, 0.50 to 0.75; P < .001), and OS (4-year OS, 69% v 60%, respectively; HR, 0.69; 95% CI, 0.54 to 0.88; P = .003). Conclusion: In this pooled analysis, CT significantly improved PFS1, PFS2, and OS. The improvement in PFS2 suggests that the benefit reported during first remission is not cancelled by a shorter second remission. PFS2 is a valuable end point to estimate long-term clinical benefit and should be included in future trials. Copyright © 2015 American Society of Clinical Oncology. All rights reserved.